The Vitamin A Story Lifting the Shadow of Death - Semba, Richard D. (Karger, 2012)
This book shows how vitamin A deficiency - before the vitamin was known to scientists - affected millions of people throughout history. It is a story of sailors and soldiers, penniless mothers, orphaned infants, and young children left susceptible to blindness and fatal infections. We also glimpse the fortunate ones who, with ample vitamin A-rich food, escaped this elusive stalker. Why were people going blind and dying? To unravel this puzzle, scientists around the world competed over the course of a century. Their persistent efforts led to the identification of vitamin A and its essential role in health. As a primary focus of today's international public health efforts, vitamin A has saved hundreds of thousands of lives. But, we discover, they could save many more were it not for obstacles erected by political and ideological zealots who lack a historical perspective of the problem.